The Effect of Role Playing Type of Cooperative Model on the Indonesian Learning Outcomes of Elementary Students - Andi Wibowo; Siti Masruro (Universitas Muhammadiyah Kalimantan Timur, 2022)
This study aims to determine the effect of the role playing type of cooperative model on student learning outcomes in the Indonesian language learning process. This study used experimental research design. Subject of this study are student in fourth grades at Kemantren 1 Elementary School. The researches variables consist of independent variable that is role playing models and lecture methods. Independent variable is the result of learning Indonesian. Students in fourth A grade as an experimental class and Fourth B grade as a control class. The instrument used in this study is the result of learning process. Data analysis techniques for cognitive domain using several steps. They are descriptive analysis, prerequisite test of normality and homogeneity, and hypothesis testing using t-test. The results showed that the role playing model influenced the learning outcomes of Indonesian language in fourth grade students at Kemantren 1 Elementary School. The average Indonesian learning in control class with the lecture method was 67,78 while the Indonesian learning outcomes in experimental class with role playing models was 74,07. Process data analysis of two groups using t-test results obtained t value of 2.896 > t table of 2.006. That is show that there are some influences in learning role playing models toward the result of Indonesian language study.